2021
DOI: 10.3310/hta25590
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation medicines and e-cigarettes: a systematic review, network meta-analysis and cost-effectiveness analysis

Abstract: Background Cigarette smoking is one of the leading causes of early death. Varenicline [Champix (UK), Pfizer Europe MA EEIG, Brussels, Belgium; or Chantix (USA), Pfizer Inc., Mission, KS, USA], bupropion (Zyban; GlaxoSmithKline, Brentford, UK) and nicotine replacement therapy are licensed aids for quitting smoking in the UK. Although not licensed, e-cigarettes may also be used in English smoking cessation services. Concerns have been raised about the safety of these medicines and e-cigarettes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 546 publications
(171 reference statements)
2
18
0
1
Order By: Relevance
“…No trials have directly compared vaping with varenicline or bupropion; however, a recent network meta-analysis of 171 RCTs by the UK National Institute for Health Research concluded that electronic cigarettes were more effective for smoking cessation than either medication. 17 The findings from RCTs are consistent with observational and population studies and the accelerated decline in smoking rates in the US and UK after vaping became widely available. [18][19][20] The role of the general practitioner GPs can assess suitability for vaping, provide additional quitting support and can write a nicotine prescription if appropriate.…”
Section: Is Vaping An Effective Quitting Aid?supporting
confidence: 73%
“…No trials have directly compared vaping with varenicline or bupropion; however, a recent network meta-analysis of 171 RCTs by the UK National Institute for Health Research concluded that electronic cigarettes were more effective for smoking cessation than either medication. 17 The findings from RCTs are consistent with observational and population studies and the accelerated decline in smoking rates in the US and UK after vaping became widely available. [18][19][20] The role of the general practitioner GPs can assess suitability for vaping, provide additional quitting support and can write a nicotine prescription if appropriate.…”
Section: Is Vaping An Effective Quitting Aid?supporting
confidence: 73%
“…shows that our finding that varenicline standard + NRT standard has the highest estimated odds ratio (OR = 5.75, 95% CrI = 2.27-14.88) is robust, but sensitive to the level of imprecision and potential biases in five studies (three rated high or unclear risk of bias), which could lead to either varenicline + bupropion standard , e-cigarette low or e-F I G U R E 3 Forest plot with results of the fixed class network meta-analysis (NMA) model for sustained abstinence (a), prolonged abstinence (b), any abstinence (c) and 7-day point prevalence abstinence (PPA) (d) cigarette high being ranked first for sustained abstinence. However, any possible biases in low/unclear risk of bias-rated studies would have to alter the OR by at least a factor of 1.6 to change the firstplace ranking.Prolonged, any abstinence and 7-day PPA Similar results to those for sustained abstinence were obtained for the other abstinence outcomes (Supporting information, Appendix, pp [29][30][31][32][33][34][35]…”
supporting
confidence: 65%
“…We used vague normal priors for all treatment effect parameters and uniform (0.5) priors for all standard deviation parameters. Full details are reported in Thomas et al [35] We also report the probability that each intervention class is ranked best, second best, and so on, across outcomes using rank-o-grams [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations